+0  
 
0
44
1
avatar

(k+1)(K-5)

Guest Mar 9, 2017

Best Answer 

 #1
avatar
+10

Expand the following:
(k + 1) (k - 5)

(k + 1) (k - 5) = (k) (k) + (k) (-5) + (1) (k) + (1) (-5):
k k + k - 5 k - 5

k k = k^2:
k^2 + k - 5 k - 5

k - 5 k = -4 k:
Answer: k^2 - 4k - 5

Guest Mar 9, 2017
Sort: 

1+0 Answers

 #1
avatar
+10
Best Answer

Expand the following:
(k + 1) (k - 5)

(k + 1) (k - 5) = (k) (k) + (k) (-5) + (1) (k) + (1) (-5):
k k + k - 5 k - 5

k k = k^2:
k^2 + k - 5 k - 5

k - 5 k = -4 k:
Answer: k^2 - 4k - 5

Guest Mar 9, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details